AN ENHANCED SYMMETRIC KEY ALGORITHM FOR SECURED NETWORK COMMUNICATION (FUDMA JOURNAL OF SCIENCES, 2023)
Sending secured messages over the internet is a challenging task for today’s network users as malicious users are increasing rapidly thereby making internet security a continuous research area. It also makes it necessary to develop a coding scheme that will enable users communicate in a more secured manner. This paper presents a review of four common symmetric key algorithms namely: Data Encryption Standard, Advanced Encryption Standard, Blowfish and RC4. The review was based on three different parameters which are key size, algorithm strengths and type of attacks related to each algorithm. The paper then proposed an enhanced symmetric key algorithm and implemented same using JAVA. The major feat of the proposed algorithm is that the generated key changes after every operation thereby providing a more secured key across the network.
Keywords: Algorithm, Encryption key, Attack, Symmetric